Released Mitochondrial DNA Following Intestinal Ischemia Reperfusion Induces the Inflammatory Response and Gut Barrier Dysfunction - Qiongyuan Hu (Nature Portfolio, 2018)
Abstract Ischemia-reperfusion (I/R) injury is a challenging clinical problem, especially injuries involving the gastrointestinal tract. Mitochondrial DNA (mtDNA) is released upon cell death and stress, and can induce the inflammatory response. We aimed to investigate the role of mtDNA in the pathogenesis of intestinal I/R. Intestinal I/R model was established with clamping of the superior mesenteric artery, and IEC-6 cells were incubated under hypoxia/reoxygenation (H/R) conditions to simulate I/R injury. Using in vitro models, H/R up-regulated oxidative stress, disrupted mitochondrial activity and the mitochondrial membrane potential, induced apoptosis and elevated the mtDNA levels in the supernatant of intestinal epithelial cells, and the co-culture of mtDNA with human primary dendritic cells significantly elevated TLR9-MyD88 expression and enhanced the production of inflammatory cytokines and chemokines. MtDNA was also released in a mouse model of intestinal I/R and was associated with the increased secretion of inflammatory cytokines and increased gut barrier injury compared with that of the sham group. We concluded that mtDNA contributes to I/R injury and may serve as a biomarker of intestinal I/R. We further suggest that oxidized mtDNA originated from IECs during intestinal I/R exacerbates the acute proinflammatory process by eliciting the production of proinflammatory cytokines and chemokines.